Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Pembinaan Karakter Siswa di SMP Islam Terpadu Siti Widhatul Faeha Ketangga Jeraeng: The Role of Principal Leadership in Improving Student Character Development at Siti Widhatul Faeha Integrated Islamic Junior High School, Ketangga Jeraeng - Ittihad; Umar Bakri; Nila Marianti; Nur Asiah Jamil; Randa Gusti Pradana (Pendidikan Al-Gafari, 2026)
Principal leadership has a very strong role in coordinating, mobilizing and harmonizing all educational resources available in the school. The purpose of this study: 1) To determine the role of principal leadership in improving the support for student character building. The type of research used is qualitative descriptive research, data was obtained by conducting observations, interviews, and documentation. The validity of the researcher's data used triangulation techniques. Data analysis was carried out in four stages, namely: data collection, data reduction, data presentation, and drawing conclusions. The results of the study show: 1. The role of principal leadership in improving the support for student character building includes: a). Visionary leader, the principal makes serious efforts by involving all school residents, b). Role model, the principal has a positive influence, c). Motivator, the principal plays an active and inspiring role, d). Innovator, the principal runs programs, such as: imtaq, congregational prayer, and scout extracurricular activities. 2. Principal leadership strategies that can be applied in improving student character building, namely by doing: a). Planning by involving BK teachers and religious teachers in coordination meetings, b). Collaborative and Participatory, collaborative emphasizes openness and active participation of all elements of the school, including parents, c). Integrating Character Values ​​in School Activities, through vision, role models, and support for positive habituation program activities, d). Evaluation is carried out in a structured and continuous manner.